2008
DOI: 10.2466/pms.107.1.293-306
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Mental Skills Program for Serving for an Intercollegiate Volleyball Team

Abstract: A preseason mental skills program for serving was implemented for the 11 members of an intercollegiate volleyball team (M age = 20.0 yr.; SD = 1.1; years of intercollegiate volleyball experience M = 2.6; SD = 0.9). Key mental skills taught were relaxation, imagery, attentional focus, goal setting, behavioral modeling, and performance routine. A videotaped behavioral model articulated and demonstrated technical performance keys to effective serving. Players utilized a three-phase service routine to increase aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 34 publications
0
10
0
6
Order By: Relevance
“…Despite this strong evidence, note however that the effects of mental training on motor performance in the sport literature are somewhat controversial. While some studies have provided clear evidences that mental training improves motor performance, for example the service in volley-ball players (Shoenfelt and Griffith 2008), other studies, see for example, the shooting in basketball, have shown that this was only partially true (Hall and Erffmeyer 1983;Lamirand and Rainey 1994).…”
Section: Features Of Motor-imagery Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this strong evidence, note however that the effects of mental training on motor performance in the sport literature are somewhat controversial. While some studies have provided clear evidences that mental training improves motor performance, for example the service in volley-ball players (Shoenfelt and Griffith 2008), other studies, see for example, the shooting in basketball, have shown that this was only partially true (Hall and Erffmeyer 1983;Lamirand and Rainey 1994).…”
Section: Features Of Motor-imagery Trainingmentioning
confidence: 99%
“…Because motor-imagery training has been repeatedly shown to improve motor performance (Debarnot et al 2009;Gentili et al 2006;Ranganathan et al 2004;Yaguez et al 1998; but see Hall and Erffmeyer 1983;Lamirand and Rainey 1994), mental training is increasingly used in sports and motor rehabilitation (Jackson et al 2001;Munzert et al 2009). For instance, mental training improves muscular force (Ranganathan et al 2004) and arm kinematics (Gentili et al 2006;Yaguez et al 1998), reduces movement variability in locomotor tasks (Courtine et al 2004), and enhances the service performance in volleyball players (Shoenfelt and Griffith 2008). Motor learning by mental training is also associated with changes in brain activation both in healthy (Jackson et al 2003;Lafleur et al 2002) and stroke patients (Page et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…T e key feature of the PE Game design is bridging physical exercise and mental empowerment via positive visualization. Visualization to improve physical function has been benef cial in diverse conditions ranging from healthy subjects (21) and competitive athletes (22) to neurologic recovery af er injury (23). Video games are emerging as attractive technologies to educate and self-empower patients to manage their diseases and accelerate their recovery.…”
Section: Healthy Video Gamesmentioning
confidence: 99%
“…Para a autoavaliação do saque, foi utilizada a Escala de Autoavaliação do Saque do Voleibol (EASV), traduzida e validada para língua portuguesa por Machado 14 , a partir da versão em inglês -Volleyball Serve-Specific Core Self-Evaluations Scale para o saque por Shoenfelt e Griffith 17 . Foram encontradas boas propriedades psicométricas para o instrumento, sendo que a consistência interna apresentou valores adequados de Alpha de Cronbach por itens e geral α= 0.87.…”
Section: Instrumentos Escala De Autoavaliação Do Saque Do Voleibolunclassified
“…É considerado uma habilidade motora fechada, estando sua execução sob o domínio do atleta 6 . Nestas condições, as tomadas de decisão sobre a execução do fundamento devem ser feitas previamente para que o executante possa realizar ação tal como programada, sem interferências contextuais.…”
Section: Introductionunclassified